2011
DOI: 10.1002/mc.20632
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal non‐catalytic subunit PSMD2 as a potential therapeutic target in association with various clinicopathologic features in lung adenocarcinomas

Abstract: We previously identified PSMD2, a subunit of the 19S regulatory complex of proteasomes, as a constituent of a signature associated with the acquisition of metastatic phenotype and poor prognosis in lung cancers. In the present study, we found that knockdown of PSMD2 decreased proteasome activity, and induced growth inhibition and apoptosis in lung cancer cell lines. These effects of siRNA-mediated PSMD2 inhibition were associated with changes in the balance between phosphorylated AKT and p38, as well as with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 35 publications
6
55
0
Order By: Relevance
“…This study also demonstrated that genes encoding components of the 26S proteasome and those involved in proteasome assembly are co-regulated in lung adenocarcinomas and a high expression of these genes is associated with shortened survival. The authors conclude that such co-regulated upregulation may confer greater advantage to cancer cell growth during cancer development 43.…”
Section: Discussionmentioning
confidence: 98%
“…This study also demonstrated that genes encoding components of the 26S proteasome and those involved in proteasome assembly are co-regulated in lung adenocarcinomas and a high expression of these genes is associated with shortened survival. The authors conclude that such co-regulated upregulation may confer greater advantage to cancer cell growth during cancer development 43.…”
Section: Discussionmentioning
confidence: 98%
“…17) and GSE11969 (90 patients in Japan; ref. 18), and the third dataset, composed entirely of lung adenocarcinoma patients, was obtained from the Shedden and colleagues study (469 patients in the United States; ref. 19).…”
Section: Microarray Processing and Survival Analysesmentioning
confidence: 99%
“…Emerging evidence has indicated that multiple subunits of proteasome were strongly implicated in regulating the biological progression of cancer cells such as proliferation, apoptosis, cell cycle, DNA repair, invasion and metastasis [4–7]. Aberration and abnormal expression of proteasome subunits have been demonstrated in many tumors including breast cancer [8], lung cancer [5, 7], hepatocellular carcinoma [9] and colorectal cancer [10]. For instance, PSMB4, a subunit of the 20S core complex, has been shown to be upregulated in epithelial ovarian cancer, and overexpression of PSMB4 was significantly related to clinicopathological characteristics and worse prognosis in epithelial ovarian cancer patients [11].…”
Section: Introductionmentioning
confidence: 99%